The Importance of Early Detection in Disease Management - Rina Setyawati; Aldiana Astuti; Tyas Putri Utami; Saputra Adiwijaya; Dadang Muhammad Hasyim (Yayasan Adra Karima Hubbi, 2024)
Early detection in disease management is a key factor in improving the effectiveness of treatment and reducing the negative impact of disease on individuals and society. The importance of early detection is a topic that is receiving increasing attention in healthcare, given the importance of identifying diseases as quickly as possible to provide appropriate treatment. This study aims to explore the importance of early detection in disease management, and to understand the positive impact of early detection on treatment outcomes and public health in general. This research utilizes the literature analysis method, by reviewing various articles, scientific journals, and reference books related to the importance of early detection in disease management. The results of the study based on the literature analysis show that early detection has a very important role in reducing mortality from disease, reducing health care costs, and improving the quality of life of patients. Early detection can also help prevent the spread of infectious diseases in the community. The conclusion of this study is that early detection in disease management has a very important role in reducing the burden of disease on individuals and society as a whole. Raising awareness of the importance of early detection, developing innovative detection technologies, and improving access to health services are some of the key steps that need to be taken to improve early detection and support effective disease management efforts.